Exploring the multidimensional impact of caregiver burden in patients with inflammatory bowel disease - Yuan Yuan; Yuan Yuan; Hao Wang; Hao Wang; Xiaomei Song; Wei Tan; Yan Liu; Hongli Liu; Chaoqun Hu; Chaoqun Hu; Hong Guo; Hong Guo (Frontiers in Public Health)
BackgroundInflammatory bowel disease (IBD) is a chronic, non-specific inflammatory condition characterized by periods of relapse and remission, often requiring frequent medical visits. Family members, who are central to the patient's social support network, often serve as primary caregivers, facing significant physiological, psychological, and financial strain. However, research on caregiver burden in IBD is limited. This study aimed to assess the current state of caregiver burden in IBD and identify contributing factors, providing a valuable reference for evaluating caregiver burden and developing targeted interventions.MethodsFrom February to December 2022, we conducted on-site questionnaire surveys with 236 IBD patients and their caregivers. The surveys collected general demographic information and utilized the Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), Pittsburgh Sleep Quality Index (PSQI), and Caregiver Burden Inventory (CBI) to assess key variables. Basic information gathered from IBD patients and their caregivers included age, health status, education level, marital status, monthly family income, the presence of co-caregivers, and daily caregiving duration.ResultsThe study included 236 IBD patients and their caregivers. We found positive correlations between CBI scores and scores on the SAS, SDS, and PSQI (r = 0.180–0.709, p < 0.01). Multiple linear regression analysis revealed that higher caregiver depression and anxiety levels, longer daily caregiving hours, younger patient age, lower patient educational level, and greater disease severity were significantly associated with increased caregiver burden. Female caregivers reported experiencing a greater burden than male caregivers.ConclusionCaregivers of IBD patients experience a substantial and multifaceted burden that is frequently underestimated. This excessive burden negatively impacts both patient outcomes and the caregiver's wellbeing, highlighting the critical need for comprehensive support from healthcare professionals and society to effectively address and alleviate caregiver burden.